EFEK ANTIDIABETES EKSTRAK AIR KULIT BUAH PISANG AMBON (Musa paradisiaca L.) TERHADAP MENCIT (Mus musculus) MODEL HIPERGLIKEMIA - Sri Indrawati; Yuliet Yuliet; Ihwan Ihwan (Universitas Tadulako, 2015)
Pisang Ambon (Musa paradisiaca L.) is one type of bananas usually consumed by Indonesian people. Besides its flesh which has high nutrition, its peels also has antioxidant activity. Antioxidants has the ability to reduce oxidative damage in people’s body with diabetes mellitus. Therefore, this study aimed to determine the antioxidant activity of the aqueous extract of Pisang Ambon peels and to determine it’s effective dose as an antidiabetic agent in hyperglycemic mice. This study used male mice which all have been intravenously induced with alloxan at a dose of 50 mg/kgBW. They were then divided into five groups. The first two groups got Na CMC 0.5% (negative control) and glibenclamide 0.65 mg/kgBW (positive control), while the other three got the aqueous extract of Pisang Ambon peels successively at doses of 400, 800, and 1200 mg/kgBW. The data were statistically analyzed using ANOVA (Analysis of Variance) at 95% confidence interval with parameter of blood glucose levels difference between before and after treatment. The results showed that the aqueous extract of Pisang Ambon peels had antidiabetic activity at an effective dose of 400 mg/kgBW in hyperglycemic mice which was comparable to glibenclamide